Oxidative pyrolysis of mallee wood biomass, cellulose and lignin - Jiang, S.; Hu, X.; Wu, L.; Zhang, Lei; Wang, Shuai; Li, T.; Xia, D.; Li, C. (Elsevier Ltd, 2018)
The oxidative pyrolysis of mallee wood, cellulose and lignin was performed and the bio-oil products were analysed to understand how the externally added oxygen react with the pyrolysis products. Both wood cylinders of diameter 8 mm and fine particles (90–300 µm) were pyrolysed in this study to understand the combined effects of biomass particle size and the presence of oxygen. The results revealed that, at a low oxygen concentration, the gas-phase oxidation of volatiles would improve the yields of levoglucosan and syringaldehyde, as well as unsaturated hydroxyl ketones/aldehydes for small wood particles through the oxygen-induced radical reactions. Although oxygen could facilitate the production of some compounds in bio-oil through the gas-phase reactions, it did lead to decreases in the heavy bio-oil yield due to the over-oxidation of some pyrolysis products (e. g. aromatics, lactones, unconjugated alkyl aldehydes/esters and carboxylic acids). The effects of oxygen on the pyrolysis of wood cylinders were more complicated than mallee wood particles due to the secondary reactions of volatiles and the reactions involving the pyrolysing particle surface. The interactions between the polysaccharide-derived and lignin-derived products in gas phase might affect the oxidation of volatiles, changing the formation of pyrolytic products (e.g. levoglucosan and syringaldehyde).